Restorasi Habitat Bekantan melalui Penanaman Mangrove Rambai (Sonneratia Caseolaris) di Pulau Curiak - Anni Nurliani; Badruzsaufari Badruzsaufari; Rusmiati Rusmiati; Rani Sasmita (Universitas Lambung Mangkurat, 2022)
The proboscis monkey's habitat is a mangrove area dominated by rambai (Sonneratia caseolaris) as their main food source. In order to suppress the rate of decline in the proboscis monkey population due to habitat loss, it is necessary to restore proboscis monkey habitat by planting rambai mangroves in their natural habitat areas, such as Curiak Island, to increase the carrying capacity of feed. So far, the rambai tree planting activity on Curiak Island is still being carried out on a self-taught basis by partners. So, there are still obstacles such as the low survival rate of seedlings, slow growth rates, challenges in transferring seedlings to planting sites, and pests and plant diseases that interfere with the growth of rambai mangroves. In this program, it has been conducted the introduction of Composter as a tool for processing organic waste into fertilizer to assist the seedling process, so that the survival of the seeds increases. Partners are also given training and counseling on the Rambai Mangrove Restoration technique with assistance starting from seed selection, transportation of seeds to planting sites, planting, and maintenance. A total of 2 composter barrels and 100 rambai mangrove seedlings have been planted with partners on Curiak Island. After this program, partners are judged to have been able to absorb the science and technology transferred by the team with an in the success of planting rambai mangroves at the planting location, Curiak Island. In future, partners are expected to independently carry out a sustainable rambai planting program so that efforts to restore proboscis monkey habitat and conserve river ecosystems can be realized.